S-nitrosothiol chemistry at the single-molecule level. - Choi, L; Bayley, H (2012)
SNO patrol: S-Nitrosothiols (RSNO) are important molecules involved in cell signaling, which control physiological processes such as vasodilation and bronchodilation. By using the protein pore α-hemolysin as a nanoreactor, the biological chemistry of RSNO has been investigated at the single-molecule level (see scheme). Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.